Review on miniaturized flexible wearable antenna with SAR measurement for body area network. (2022) - Pandey, Utkarsh; Singh, Parulpreet; Singh, Raghvendra
Abstract: The existence of Body area network (BAN) is present at the proximity of human body comprising of gadgets put in, on and close with regard to person's body. This BAN is comprising of embedded devices which communicate information through different channel to other devices. Basically, these devices utilize electromagnetic innovations for making device handier and more useful. It can be broadly seen as this could be utilized in three different manners. The application of BAN is truly valuable in many different medical applications. First is in observing the sensors' performance which has been inserted inside the body of patients. Second is following record of wellbeing of older folks. Third is many modern testing techniques such as MRI, CT-Scan, endoscopic test etc. BAN is being used in so many useful functions. It's an obtrusive, low power and handy system comprising of high data security. Looking at the usefulness of the wearable antennas under BAN. In the presented study a review on various aspects required to be gone through while designing antenna to work in BAN. and various methods to get minimum errors by discussing different configurations of MSP (Micro strip patch) has been discussed. Through this review paper the designing and analysis of various body worn antennas applicable in BAN working under different situations has been done which is really helpful in construction of wearable flexible antenna for BAN.